The Effect of Governance on FDI Inflows in ASEAN - Ranynda Niarachma; Nury Effendi; Eva Ervani (Optimum: Jurnal Ekonomi dan Pembangunan, 2021)
This study examines the effect of governance on FDI inflows in ASEAN countries for the period 2002-2018 using the Worldwide Governance Indicator (WGI) index. This study uses a principal component analysis (PCA) method to reduce six WGI indexes and performs panel data regression analysis using fixed-effect GLS (cross-section weights). This study uses data from World Bank for FDI, WGI, and several control variables. Â The results of this study have provided empirical evidence that good governance is a very important key factor in encouraging FDI inflows to host countries. This study finds three governance elements that have a positive relationship with FDI inflows in ASEAN countries are the quality of regulations, rule of law, and control of corruption.Â